The Rationality of Indigenous Accountability: Bali's Indigenous Village Accountability Practices - Surya, Luh Putu Lusi Setyandarini (E-Jurnal Akuntansi, 2024)
Accountability, at its core, is the duty to report on and justify the fulfillment of responsibilities to the party that has entrusted those responsibilities. This study seeks to explore and conceptualize the rationale behind accountability in Traditional Village within Bali Province, grounded in the Tri Hita Karana philosophy. This article uses a literature review to explore the rationale behind accountability practices within the context of the local Balinese philosophy of Tri Hita Karana. By examining these two perspectives, it seeks to conceptualize a framework for accountability that is rational for the Balinese Traditional Village community organization. Based on the Tri Hita Karana philosophy, the rationale for accountability in Traditional Villages extends beyond formal financial reporting, encompassing spiritual and religious dimensions, regulatory and economic dimensions, and environmental considerations.